2019
DOI: 10.2196/14210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Digital Device Ownership on Cognitive Decline in a Middle-Aged and Elderly Population: Longitudinal Observational Study

Abstract: Background Cognitive decline is a major risk factor for disability and death and may serve as a precursor of dementia. Digital devices can provide a platform of cognitively stimulating activities which might help to slow cognitive decline during the process of normal aging. Objective This longitudinal study aimed to examine the independent protective factors of desktop and cellphone ownership against cognitive decline in mid-life and older adulthood and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 37 publications
4
49
0
2
Order By: Relevance
“…Indeed compared to traditional brain training computers, smartphones, and virtual environments offer interesting possibilities indeed computerized model could bring more complex environment that will challenge and impact cognition more than traditional exercises 59 . Another potential positive aspect of having the training on smartphones is that recent studies underlined the importance of digital devices as platforms for cognitively stimulating activities in delaying cognitive decline in older adults 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed compared to traditional brain training computers, smartphones, and virtual environments offer interesting possibilities indeed computerized model could bring more complex environment that will challenge and impact cognition more than traditional exercises 59 . Another potential positive aspect of having the training on smartphones is that recent studies underlined the importance of digital devices as platforms for cognitively stimulating activities in delaying cognitive decline in older adults 60 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 38 For learning activities, studies showed that internet use provided important platforms for cognitively stimulating activities to delay cognitive decline. 24 Learning activities may generate a cognitive reserve buffer that promotes resilience to prevent or delay the development of cognitive impairment. 39 Our results underscored the importance of attending different types of social engagement for delaying the process of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In the CHARLS Survey, cognitive function was measured through a global cognitive function score based on two aspects of cognitive functions: episodic memory and mental intactness. 24 25 For episodic memory, each participant was asked to repeat as many as possible 10 Chinese nouns just read to him/her (immediate word recall), and then to recall the same 10-word list 5 min later (delayed recall). Answers to these questions were aggregated into a single episodic memory score ranging from 0 to 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the elderly constitute the major part of the population suffering disabilities, such findings may be a further argument for supporting the use of computer and the Internet by the elderly. Interesting results have been reported recently by Jin et al [45]. They analysed the data from a longitudinal study encompassing a cohort of 13,457 Chinese adults.…”
Section: Discussionmentioning
confidence: 99%